Performance Investigation of Grid Connected Photovoltaic System Modelling Based on MATLAB Simulation - Adnan Hussein Ali; Hassan Salman Hamad; Ali Abdulwahhab Abdulrazzaq (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Photovoltaic (PV) systems are normally modeled by employing accurate equations dealing with a behavior the PV system. This model has Characteristic of PV array cells, which are influenced by both irradiation and temperature variations. Grid-connected PV system is considered as electricity generated solar cell system which is connected to the grid utilities. This paper characterizes an exhibiting and simulating of PV system that executed with MATLAB /Simulink. The impact of solar irradiances as well as ambient temperature performances of PV models is investigated and noted that a lower temperature provides maximum power higher so that the open circuit voltage is larger. Furthermore, if the temperature is low, then a considerably short circuit current is low too.